DNA methylation signatures of chronic low-grade inflammation are associated with complex diseases. Issue 1 (December 2016) - Ligthart, Symen; Marzi, Carola; Aslibekyan, Stella; Mendelson, Michael; Conneely, Karen; Tanaka, Toshiko; Colicino, Elena; Waite, Lindsay; Joehanes, Roby; Guan, Weihua; Brody, Jennifer; Elks, Cathy; et al.
Abstract Background Chronic low-grade inflammation reflects a subclinical immune response implicated in the pathogenesis of complex diseases. Identifying genetic loci where DNA methylation is associated with chronic low-grade inflammation may reveal novel pathways or therapeutic targets for inflammation. Results We performed a meta-analysis of epigenome-wide association studies (EWAS) of serum C-reactive protein (CRP), which is a sensitive marker of low-grade inflammation, in a large European population (n = 8863) and trans-ethnic replication in African Americans (n = 4111). We found differential methylation at 218 CpG sites to be associated with CRP (P < 1.15 × 10–7 ) in the discovery panel of European ancestry and replicated (P < 2.29 × 10–4 ) 58 CpG sites (45 unique loci) among African Americans. To further characterize the molecular and clinical relevance of the findings, we examined the association with gene expression, genetic sequence variants, and clinical outcomes. DNA methylation at nine (16%) CpG sites was associated with whole blood gene expression in cis (P < 8.47 × 10–5 ), ten (17%) CpG sites were associated with a nearby genetic variant (P < 2.50 × 10–3 ), and 51 (88%) were also associated with at least one related cardiometabolic entity (P < 9.58 × 10–5 ). An additive weighted score of replicated CpG sites accounted for up to 6% inter-individual variation (R2) of age-adjusted and sex-adjusted CRP, independent of known CRP-related genetic variants. Conclusion We have completed an EWAS of chronic low-grade inflammation and identified many novel genetic loci underlying inflammation that may serve as targets for the development of novel therapeutic interventions for inflammation.